The Relation Between Valence and Arousal in Subjective Experience Varies With Personality and Culture. Issue 4 (28th May 2016) - Kuppens, Peter; Tuerlinckx, Francis; Yik, Michelle; Koval, Peter; Coosemans, Joachim; Zeng, Kevin J.; Russell, James A.
Abstract: Objective: While in general arousal increases with positive or negative valence (a so‐called V‐shaped relation), there are large differences among individuals in how these two fundamental dimensions of affect are related in people's experience. In two studies, we examined two possible sources of this variation: personality and culture. Method: In Study 1, participants (Belgian university students) recalled a recent event that was characterized by high or low valence or arousal and reported on their feelings and their personality in terms of the Five‐Factor Model. In Study 2, participants from Canada, China/Hong Kong, Japan, Korea, and Spain reported on their feelings in a thin slice of time and on their personality. Results: In Study 1, we replicated the V‐shape as characterizing the relation between valence and arousal, and identified personality correlates of experiencing particular valence–arousal combinations. In Study 2, we documented how the V‐shaped relation varied as a function of Western versus Eastern cultural background and personality. Conclusions: The results showed that the steepness of the V‐shaped relation between valence and arousal increases with Extraversion within cultures, and with a West‐East distinction between cultures. Implications for the personality–emotion link and research on cultural differences in affect are discussed.